The cracking of Scots pine (Pinus sylvestris) cones - Horstmann, Martin; Buchheit, Hannah; Speck, Thomas; Poppinga, Simon (Frontiers in Plant Science, 2022)
Pine cones show functionally highly resilient, hygroscopically actuated opening and closing movements, which are repeatable and function even in millions of years old, coalified cones. Although the functional morphology and biomechanics behind the individual seed scale motions are increasingly well understood, the initial opening of the cone, which is often accompanied by an audible cracking noise, is not. We therefore investigated the initial opening events of mature fresh cones of Scots pine (Pinus sylvestris) and their subsequent motion patterns. Using high-speed and time lapse videography, 3D digital image correlation techniques, force measurements, thermographic and chemical-rheological resin analyses, we are able to draw a holistic picture of the initial opening process involving the rupture of resin seals and very fast seed scale motion in the millisecond regime. Based on our results, we propose an interplay of humidity and temperature to be responsible for an ecologically optimized timing of (first) cone opening and seed release, in which resin works as a crucial chemical-mechanical latch system.